Correlation between serum homocysteine level and clinicopathological factors of IgA nephropathy - Cai Xiao-fan; Huang Jie-bo; Xing Yue; Cai Xiu-feng; Li Xue-ling; Zhong Yi-fei (Linchuang shenzangbing zazhi)
ObjectiveTo investigate the correlation between serum homocysteine （Hcy） and clinicopathologic factors of immunoglobulin A nephropathy （IgAN）.MethodsA total of 349 patients with IgAN diagnosed by renal biopsy in the Nephrology Department of Longhua Hospital， Shanghai University of Traditional Chinese Medicine from January 1， 2014 to October 31， 2023 were retrospectively analyzed. The patients were divided into the Hcy normal group and hyperhomocysteinemia （HHcy） group according to Hcy level at the time of renal biopsy. Clinical observation data and pathological injury indices were compared between groups. The correlation of estimated glomerular filtration rate （eGFR） and pathological injury indices with Hcy was analyzed by Spearman's correlation analysis. The clinicopathological factors associated with HHcy were analyzed by logistic regression， and area under the receiver operator characteristic curve （AUC） was used to assess the ability of Hcy in predicting pathologic injuries associated with IgAN.ResultsPatients in the HHcy group had significantly higher male ratio （63.1% vs 32.7%）， age ［（40.44 ± 12.85）years vs （36.83 ± 11.56）years］， albumin ［Alb，（38.14 ± 4.71）g/L vs （36.28 ± 6.65）g/L］， serum creatinine ［Scr，（125.90 ± 75.89）μmol/L vs （75.39 ± 29.16）μmol/L］， blood uric urea ［BUN，（7.61 ± 4.01）mmol/L vs （5.29 ± 1.78）mmol/L］， uric acid ［UA，（427.04 ± 101.99）μmol/L vs （351.56 ± 93.45）μmol/L］， and cystatin C ［Cys C，（1.61 ± 0.66）mg/L vs （1.05 ± 0.36）mg/L］， but lower eGFR ［（70.50 ± 30.90）mL·min-1·（1.73 m2）-1 vs （100.35 ± 27.08）mL·min-1·（1.73 m2）-1］ than the Hcy normal group （all P<0.05）. Renal tubular atrophy and renal interstitial fibrosis （T， 42.5% vs 16.3%） and thickening of renal arteriolar wall （A， 73.8% vs 49.5%） were significantly larger in the HHcy group than the Hcy normal group （all P<0.05）. Spearman correlation showed that Hcy was negatively correlated with eGFR， but positively correlated with T and A （all P<0.05）. Logistic regression showed that sex， Alb， Scr， Cys C， T and A was significantly correlated with HHcy （all P<0.05）. The AUC of Hcy in predicting T and A was 0.751 （95%CI：0.699-0.803） and 0.625 （95%CI：0.565-0.685）， respectively， with the optimal cut-off value of 15.04 μmol/L and 13.11 μmol/L， respectively （all P<0.05）.ConclusionsHcy level at renal biopsy is significantly correlated with sex， Alb， Scr， Cys C， T and A in patients with IgAN， showing a potential ability to predict associated damages.